2022
DOI: 10.1177/17588359221119538
|View full text |Cite
|
Sign up to set email alerts
|

Survival benefit of HER2-targeted or androgen deprivation therapy in salivary duct carcinoma

Abstract: Background: The efficacy and safety of human epidermal growth factor receptor 2 (HER2)-targeted therapy and androgen deprivation therapy (ADT) for locally advanced or recurrent or metastatic (LA/RM) salivary duct carcinoma (SDC) have been reported in prospective studies. However, the survival benefit of these therapies to conventional therapy remains controversial, and whether HER2-targeted therapy or ADT should be chosen in HER2- and androgen receptor (AR)-positive SDC patients remains unknown. Methods: Overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Studies with anti-HER-2 therapies showed that ORR was more than 50% in patients with SDC. Chemotherapy combined with HER-2 blockade included docetaxel in three studies [23, 24, 26], pertuzumab in one [25], and docetaxel with pertuzumab in another [28]. Trials with feasible ORR only targeted SDC [23, 24, 26, 28] and not the whole SGC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies with anti-HER-2 therapies showed that ORR was more than 50% in patients with SDC. Chemotherapy combined with HER-2 blockade included docetaxel in three studies [23, 24, 26], pertuzumab in one [25], and docetaxel with pertuzumab in another [28]. Trials with feasible ORR only targeted SDC [23, 24, 26, 28] and not the whole SGC.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy combined with HER-2 blockade included docetaxel in three studies [23, 24, 26], pertuzumab in one [25], and docetaxel with pertuzumab in another [28]. Trials with feasible ORR only targeted SDC [23, 24, 26, 28] and not the whole SGC. HER-2-targeted therapy cannot be applied to a large range of patients with SGC because HER-2, except in SDC, is not commonly expressed in SGC [29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations